Control effects and mechanisms of metabolites from Streptomyces ahygroscopicus var. gongzhulingensis strain 769 on sclerotinia rot in sunflowers - Liu, Zhiming; Lu, Yang; Li, Qiyun; Xie, Zhao; Sui, Li; Gong, Shufang; Zhang, Zhengkun (Frontiers in Plant Science, 2025)
Introduction‌Sunflower sclerotinia rot caused by Sclerotinia sclerotiorum poses a significant threat to global agriculture. This study investigates Streptomyces ahygroscopicus var. gongzhulingensis 769 (S769) as a novel biocontrol agent against this devastating disease.Methods‌‌Antagonism assays evaluated S769's efficacy in vitro, while detached leaf, pot, and field trials assessed disease suppression through soil mixing (S769-Ms) and root drenching (S769-i). Mechanistic analyses included enzyme activity assays, microbiome profiling, qPCR quantification of pathogen load, and root transcriptomics.Results‌‌S769 exhibited 65.79% mycelial growth inhibition in vitro. Field trials demonstrated significant disease control (S769-Ms: 7.36%, S769-i: 5.92% vs. 14.69% control), with 15.85% increase in root fresh weight and 34.26% reduction in shriveled seeds. qPCR confirmed 4.85-fold pathogen reduction in leaves and 2.68-fold in roots. Transcriptomics revealed 6,622 upregulated genes, including MAPK signaling and phenylpropanoid biosynthesis pathways.Discussion‌‌S769 demonstrates dual action through direct antifungal effects and host defense activation. The enrichment of beneficial rhizobacteria (Sphingomonas, Chitinophagaceae) without altering microbial diversity highlights its potential as a sustainable agricultural solution for sclerotinia rot management.